Zhuifeng Tougu capsules in the treatment of knee osteoarthritis (cold dampness obstruction syndrome): a randomized, double blind, multicenter clinical study - Longmei Zhao; Shasha Zhou; SiWei Wang; Rui Wu; Qingliang Meng; Zhenbin Li; Jiangyun Peng; Ying Liu; Min Lu; Ming Li; Caifeng Zhu; Yue Sun; et al. (BMC, 2024)
Abstract Background In Traditional Chinese Medicine (TCM) theory, cold dampness obstruction is one of the common syndromes of osteoarthritis. Therefore, in clinical practice, the main treatment methods are to dispel wind, remove dampness, and dissipate cold, used to treat knee osteoarthritis (KOA). This report describes a mulitercenter clinical study to assess Zhuifeng Tougu Capsule's efficacy and safety in the treatment of patients who are cold dampness obstruction syndrome in KOA, and to provide evidence-based medical for the rational use of Zhuifeng Tougu Capsules in clinical practice. Methods This randomized, parallel group controlled, double-blind, double dummy trial will include a total of 215 KOA patients who meet the study criteria. 215 patients underwent 1:1 randomisation, with 107 cases assigned the experimental group (Zhuifeng Tougu Capsules + Glucosamine Sulfate Capsules Simulator) and 108 assigned the control group (Glucosamine Sulfate Capsules + Zhuifeng Tougu Capsules Simulator). After enrolment, patients received 12 weeks of treatment. The main efficacy measure is the Western Ontario and McMaster University Osteoarthritis Index (WOMAC) pain score. Visual analogue scale (VAS) pain score, Self-condition assessment VAS score, WOMAC KOA score, TCM syndrome score and TCM syndrome efficacy, ESR level, CRP level, suprapatellar bursa effusion depth, use of rescue drugs, and safety indicators are secondary efficacy indicators. Results Compared with before treatment, WOMAC pain score, VAS pain score, Self-condition assessment VAS score, WOMAC KOA score, and TCM syndrome score decreased significantly in both groups (P < 0.01). Also, the experimental group showed significant differences in the above indicators compared to control (P < 0.01). However, after treatment, no significant differences were showed in the ESR level, CRP level, and suprapatellar bursa effusion depth between the two groups (P > 0.05). No any serious adverse effects showed in the experimental group and control group. Conclusions Zhuifeng Tougu Capsules can effectively improve knee joint function and significantly alleviate the pain of KOA. Trial registration: Clinical trial registration was completed with the China Clinical Trial Registration Center for this research protocol (No. ChiCTR2000028750) on January 2, 2020.